Efficient Forster Resonance Energy Transfer Donors of In(Zn)P/ZnS Quantum Dots - Altintas, Yemliha; Talpur, Mohammad Younis; Mutlugun, Evren; Altlntas, Yemliha (Amer Chemical Soc, 2017)
We demonstrate a detailed investigation of the effect of the type and concentration of zinc precursor on the optical properties of In(Zn)P/ZnS quantum dots. We achieved up to 87% quantum yield along with 54 nm emission bandwidth for the green emitters with changing the concentration of the Zn precursors. Employing efficient green emitters as the donor species, we demonstrated an efficient Forster resonance energy transfer (FRET) couple of green and red emitting InP-based quantum dots. With a FRET efficiency level of 70.3% achieved (analyzed from the donor lifetime with and without an acceptor), we further demonstrated the enhancement of the acceptor emission nearly twofold due to the energy transfer. Our results provide new insights toward the understanding of the excitonic interactions among donor and acceptor quantum dots of the III-V family for light harvesting applications.
Mutlugun, Evren/0000-0003-3715-5594; Talpur, Dr. M.Younis/0000-0001-6361-1579;